Administrative law in Malaysia - Ahmad, Wan Azlan; Nik Mahmod, Nik Ahmad Kamal (Sweet & Maxwell Asia, 2006)
Power of a public nature must neither be abused nor exceeded. Administrative law is the branch of public law which is principally concerned with ensuring that the government, government departments, tribunals and all authorities exercising public law functions act within the perimeters of their power. Judicial review is the backbone of administrative law and is the most potent judicial weapon available to an aggrieved individual to challenge the validity of the decision-making process of public authorities.